Askåterföring i Jämtland : biobränslets och askans innehåll av tungmetaller relaterat till markernas geokemi - Backlund, Ingegerd (SLU/Dept. of Forest Soils, 2007)
Using biofuels from regeneration cuttings is becoming more common in Sweden. Ash from the combustion of biofuels contains many valuable nutrients and base cations. The Swedish Forest Agency recommends that ash should be recycled to clearings where biofuels have been removed, to avoid future impoverishment of Swedish woodlands. In Jämtland, in northern Sweden, a large quantity of biofuels are taken out from cuttings but ash recycling has not yet been tried. The aim of this thesis was to examine the conditions for ash recycling in Jämtland regarding to soil chemistry and heavy metal content in soil and biofuels. To achieve that, a survey of which soils that are most suitable for ash recycling was included; and the heavy metal content in biofuels was examined, to see if biofuels from areas with large metal amounts in the soil contained more heavy metals than other biofuels. Twenty biofuel samples were collected from incoming transports from the woodlands of Jämtland to the heatand power plant in Östersund. The material was dried and sorted into needle fractions and branch fractions. The material was then milled. Analyses of As, Cr, Pb, Hg, Ni, Cu, Cd and Zn were carried out by ICPMS. The results show that needles from Jämtland contain more heavy metals and arsenic than needles from other regions in Sweden. Branches from Jämtland do not contain more heavy metals and arsenic than average. Three samples of non sorted biofuel material were also analyzed by ICPMS. The results show that they contain more heavy metals than the sorted and brushed material taken from the same places. This can be due to occurrence of minerogenic materials in the nonsorted samples. The correlation between heavy metal concentrations in soil and needles, as well as the correlation between heavy metal concentrations in soil and branches, were both weak. The reasons for this can be that the heavy metal concentrations in soil vary a lot in a small area. Suitable lands for ash recycling in Jämtland are mainly the area around the lake Storsjön. ...